PROFESSIONAL-PEDAGOGICAL REFLECTION OF STUDENTS: RESULTS OF EMPIRICAL RESEARCH WORK - M. N. Dudina (Образование и наука)
Introduction. Today, questions of valuable preferences and priorities of young people choosing a career in teaching are attracting widespread interest due to the introduction of new educational standards and subsequently fullygrown social and state requirements for teaching professionals. Individual characteristics (own intensions, potentialities, achievements) of future teachers have to correspond ideally to a humanistic educational paradigm and personally focused model of training and education.The aim of this research is to clarify the specifics of students’ reflection on the acquired profession and seeing themselves as future teachers.Methodology and research methods. The methodological framework of the study is based on competencyand system-based approaches. The author’s technique built upon a questionnaire was the main research tool. The technique of psychometric diagnostics offered by S. A. Minyurova and A. I. Kalashnikov became initial material for drawing up tasks of the questionnaire; that diagnostics is designed for measurement of professional commitment of school teachers and adapted to study reflexive sphere of students’ personality who chose pedagogical field of study. The non-parametric Mann-Whitney U-criterion test was applied when processing the data obtained during the questionnaire to compare average values of independent samples of respondents.Results and scientific novelty. The carried out analysis of dynamically changing external and internal (objective and subjective) allowed the author to emphasize the factors that influence students’ motivation to pedagogical activity, desire to realize themselves in it, and aspirations to study “through all life”. The proposed by the author new technique of a self-assessment for students with different levels of higher pedagogical education including postgraduate is approved. Significantly, the technique enables to reveal: socially and personally significant purposes of future teachers and lecturers; their valuable orientations; levels of adequacy for reflection of their personal attitudes to pedagogical activity; students’ ability to realize own professional competence and pedagogical marginalization. Successful approbation of the trial version of new methodical tools showed that selfassessment of future teachers significantly correlates with recognition of great demands of society required to a pedagogical profession.Practical significance. The research materials will be useful in psychological and pedagogical support for students when designing individual educational paths of pedagogical professional development.